2018
DOI: 10.31230/osf.io/crkvn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consistent microplastic ingestion by deep-sea invertebrates over the last four decades (1976–2015), a study from the North East Atlantic

Abstract: Although evidence suggests the ubiquity of microplastics in the marine environment, our knowledge of its occurrence within remote habitats, such as the deep sea, is scarce. Furthermore, long term investigations of microplastic abundances are even more limited. Here we present a long-term study of the ingestion of microplastics by two deep-sea benthic invertebrates (Ophiomusium lymani and Hymenaster pellucidus) sampled over four decades. Specimens were collected between the years 1976–2015 from a repeat monitor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The interest in distinguishing among contourites, turbidites and hemipelagites based on: (i) the role of mixed turbiditic-contouritic systems in deep-water petroleum plays (Sansom, 2018;Fonnesu et al, 2020); (ii) implications for mineral resources and for the judicial determination of a continental shelf´s outer limits since contourites shape continental shelf morphology (Rebesco et al, 2014;Mosher et al, 2017); (iii) the environmental impact of bottom current deposits in the accumulation of microplastics (Courtene-Jones et al, 2019;Kane et al, 2020); (iv) the close link between contourites and deep-water ecosystems (Hebbeln et al, 2016;L€ udmann et al, 2016;Lozano et al, 2020); and (v) slope stability and other geohazards (Laberg & Camerlenghi, 2008;Miramontes et al, 2018). Despite this interest, there is still no clear criteria for contourite characterization and its discrimination from other deep-water deposits.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in distinguishing among contourites, turbidites and hemipelagites based on: (i) the role of mixed turbiditic-contouritic systems in deep-water petroleum plays (Sansom, 2018;Fonnesu et al, 2020); (ii) implications for mineral resources and for the judicial determination of a continental shelf´s outer limits since contourites shape continental shelf morphology (Rebesco et al, 2014;Mosher et al, 2017); (iii) the environmental impact of bottom current deposits in the accumulation of microplastics (Courtene-Jones et al, 2019;Kane et al, 2020); (iv) the close link between contourites and deep-water ecosystems (Hebbeln et al, 2016;L€ udmann et al, 2016;Lozano et al, 2020); and (v) slope stability and other geohazards (Laberg & Camerlenghi, 2008;Miramontes et al, 2018). Despite this interest, there is still no clear criteria for contourite characterization and its discrimination from other deep-water deposits.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined historical specimens for microplastics, but have not shown a temporal trend in concentration. For example, Courtene‐Jones et al (2019) found that microplastic concentrations in deep‐sea invertebrates did not increase significantly from the 1970s to 2015. Beer et al (2018) studied marine fish collected from 1980s to 2010s and found there were no significant differences in microplastic concentration over time.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on plankton and forage fish have taken great care to thoroughly clean specimens externally prior to digestion or dissection, and to focus solely on whole organisms rather than on pre-dissected tissues, which carry a higher risk of contamination from the surroundings in which samples were processed, sometimes decades previously. 176,184,185…”
Section: Sampling and Qa/qc Considerations For Each Matrixmentioning
confidence: 99%
“…Recent studies on plankton and forage fish have taken great care to thoroughly clean specimens externally prior to digestion or dissection, and to focus solely on whole organisms rather than on pre-dissected tissues, which carry a higher risk of contamination from the surroundings in which samples were processed, sometimes decades previously. 176,184,185 Necropsies of deceased individuals can provide information on diet as well as exposure to microplastics. This approach has been applied to birds for many years and has been recommended for monitoring within Oslo/Paris Convention for the Protection of the Marine Environment of the Northeast Atlantic.…”
Section: Biotamentioning
confidence: 99%